The Factors Influencing the Earnings Management in Indonesian State-Owned Enterprise Listed on the Indonesia Stock Exchange from 2016-2020 - Zaneta Millinea Renata; Imanuel Madea Sakti (Universitas Pendidikan Ganesha, 2022)
Managers' efforts to provide added value to the company can lead to conflicts of interest between agents (managers) and principals (owners). Problems may occur when relying on managers to control the company to improve company performance. This study aims to examine the factors that affect earnings management. This type of research is quantitative by using explanatory (Explanatory Research). The population in this study is State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange. The sample of this research is 20 BUMN listed on the Indonesia Stock Exchange from 2016-2020. The sampling technique used is purposive sampling. The technique used to analyze the data is inferential statistical analysis. The hypotheses were tested using panel data regression analysis. The results showed that profitability and leverage positively affected earnings management, while size did not affect earnings management. This finding shows that SOEs' profit-generating factors and debt ownership motivate management to carry out good earnings management for their shareholders.